2016
DOI: 10.1111/acer.13258
|View full text |Cite
|
Sign up to set email alerts
|

Withdrawal from Chronic Nicotine Exposure Produces Region‐Specific Tolerance to Alcohol‐Stimulated GluA1 Phosphorylation

Abstract: Background Nicotine use increases alcohol drinking, suggesting that the combination of these drugs may produce synergistic effects in activating reward circuitry. Alternatively, use of either of these drugs may facilitate the development of cross-tolerance to the other to promote intake escalation. Methods In the current study, adult male Wistar rats were chronically exposed to room air or chronic, intermittent nicotine vapor, which has been shown to produce symptoms of nicotine dependence as evidenced by el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…Air nicotine concentrations in the 1-10 mg/m 3 range closely mimic conditions of human smoking. Moreover, other groups (Baiamonte et al, 2014;McGinn et al, 2016;Xue et al, 2018) have replicated our original findings, showing that the delivery of 7 mg/m 3 nicotine at 10 L/min produced nicotine dependence with somatic signs of withdrawal and hyperalgesia, similar to other animal models (e.g., minipumps and intravenous self-administration), and blood nicotine levels in the 10-100 ng/ml range. Another limitation of the present study was that we included male adolescent rats only.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Air nicotine concentrations in the 1-10 mg/m 3 range closely mimic conditions of human smoking. Moreover, other groups (Baiamonte et al, 2014;McGinn et al, 2016;Xue et al, 2018) have replicated our original findings, showing that the delivery of 7 mg/m 3 nicotine at 10 L/min produced nicotine dependence with somatic signs of withdrawal and hyperalgesia, similar to other animal models (e.g., minipumps and intravenous self-administration), and blood nicotine levels in the 10-100 ng/ml range. Another limitation of the present study was that we included male adolescent rats only.…”
Section: Discussionsupporting
confidence: 82%
“…We tested the effects of two concentrations of nicotine vapor (0.4 and 7 mg/m 3 ) over 7 days of exposure (14 h/day). Intermittent nicotine vapor exposure, with 14 h vapor ON and 10 h OFF, was used based on previous studies (Baiamonte et al, 2014;Gilpin et al, 2014;McGinn et al, 2016;Xue et al, 2018) that showed that this protocol produces nicotine dependence with somatic signs of withdrawal and hyperalgesia when exposed to high levels of nicotine (7 mg/m 3 ). This protocol is highly relevant to adolescent e-cigarette users, who often vape intermittently because of either parental or societal restrictions.…”
Section: Introductionmentioning
confidence: 99%
“…Western blot analyses for brain regional changes in protein phosphorylation were conducted as previously described (McGinn et al, 2016) in animals from group 1. Rats were sacrificed by decapitation under light isoflurane anesthesia 24 hours after the last injection (Figure 2A).…”
Section: Methodsmentioning
confidence: 99%
“…Animals were sacrificed by decapitation under isoflurane anesthesia 2 weeks post-TBI, and brains were excised, flash frozen, and analyzed as previously described. 43 Ventral striatum and central amygdala punches were obtained from 0.5-mm frozen coronal brain slices and homogenized by sonication in lysis buffer (320 mM sucrose, 5 mM 4(2-hydroxyethyl)-1-piperazineethanesulfonic acid [HEPES], 1 mM egtazic acid [EGTA], 1 mM ethylenediaminetetraacetic acid [EDTA], and 1% sodium dodecyl sulphate [SDS], with protease inhibitor cocktail and phosphatase inhibitor cocktails II and III diluted 1:100; Sigma, St. Louis, MO). Protein concentration was determined by the Lowry method (Bio-Rad, Hercules, CA), and 20-lg protein samples were separated by SDSpolyacrylamide gel electrophoresis (SDS-PAGE) on 4-15% gradient acrylamide gels before transfer to polyvinylidene difluoride membranes (GE Healthcare, Piscataway, NJ).…”
Section: Western Blot Analysismentioning
confidence: 99%